2011
DOI: 10.3389/fpsyt.2011.00014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thalamic Projection in NMDA Receptor-Induced Disruption of Cortical Slow Oscillation and Short-Term Plasticity

Abstract: NMDA receptor (NMDAR) antagonists, such as phencyclidine, ketamine, or dizocilpine (MK-801) are commonly used in psychiatric drug discovery in order to model several symptoms of schizophrenia, including psychosis and impairments in working memory. In spite of the widespread use of NMDAR antagonists in preclinical and clinical studies, our understanding of the mode of action of these drugs on brain circuits and neuronal networks is still limited. In the present study spontaneous local field potential (LFP), mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 73 publications
3
58
0
3
Order By: Relevance
“…The objective of this study was to quantify the effects of systemically administered PF-4778574 on the cortical disruption of electroencephalogram (EEG) and paired-pulse facilitation (PPF) by the noncompetitive NMDAR antagonist MK-801 in urethaneanesthetized Sprague-Dawley rats (Kiss et al, 2011b). This is a preclinical model, which evaluates the subiculum-medial PFC pathway, proposed for studying NMDAR hypofunction of schizophrenia.…”
Section: In Vivo Pharmacologymentioning
confidence: 99%
“…The objective of this study was to quantify the effects of systemically administered PF-4778574 on the cortical disruption of electroencephalogram (EEG) and paired-pulse facilitation (PPF) by the noncompetitive NMDAR antagonist MK-801 in urethaneanesthetized Sprague-Dawley rats (Kiss et al, 2011b). This is a preclinical model, which evaluates the subiculum-medial PFC pathway, proposed for studying NMDAR hypofunction of schizophrenia.…”
Section: In Vivo Pharmacologymentioning
confidence: 99%
“…However, a 4-week treatment reversed the magnitude of LTP to control level. Intrathalamic administration of MK-801 changes local field potentials and paired-pulse facilitation in rats, indicative of changes in short-term plasticity (Kiss et al, 2011). After application of MK-801, homosynaptic LTP of the direct cortical input to CA1 was abolished for at least 1 week, with partial recovery after 4 weeks (Wöhrl et al, 2007).…”
Section: F N-methyl-d-aspartate Receptor Antagonistsmentioning
confidence: 99%
“…Several studies have shown that the PFC and MD are the predominant sites mediating the actions of non-competitive NMDAR antagonists, including changes in neurotransmission and behaviour (Amargós-Bosch et al 2006;López-Gil et al 2007;Kargieman et al 2007;Zhang et al 2009Zhang et al , 2012Santana et al 2011;Kiss et al 2011;López Hill and Scorza 2012). Furthermore, it has been proposed that PCP acts on the cortico-thalamo-cortical circuit involving the PFC, RS 15 and thalamus (Celada et al 2013).…”
Section: Pcp-induced C-fos-ir In the Pfc And MDmentioning
confidence: 99%
“…There are, however, some differences in the degree of PCP-induced c-Fos-IR in these regions -suggesting that different mechanisms might contribute to the effects of PCP, or that the primary PCP-mediated activation is at an afferent site that projects stronger to the VLO and RS than the mPFC. Studies have shown that whereas systemic administration of non-competitive NMDAR antagonists leads to PFC and MD hyperactivity, locally injected antagonists in the PFC has no effect on the activity of PFC neurons (Suzuki et al 2002;Jodo et al 2005;Kiss et al 2011) suggesting excitatory inputs to the PFC to be involved in the actions of non-competitive NMDAR antagonists. Further, local MK-801 administration into the MD produces effects similar to systemically injected MK-801 (Kiss et al 2011) indicating that non-competitive NMDAR antagonists act on circuit level at thalamic areas.…”
Section: Pcp-induced C-fos-ir In the Pfc And MDmentioning
confidence: 99%
See 1 more Smart Citation